Event Study: Capital Market Reaction Before and After the Announcement of Presidential and Vice Presidential Candidates 2024 - Sasi Kirana Hayumurti; Khomsiyah (Owner : Riset dan Jurnal Akuntansi, 2025)
This study aims to determine the reaction of the capital market before and after the announcement of the 2024 election. This study is an event study using abnormal returns to test the reaction of the capital market to one of the national political events, the announcement of the disputed results of the 2024 presidential election. This study also investigates the difference in abnormal returns, which occurs between the date of the event and the date after the event. The population of this study is the shares of companies whose owners are affiliated with the elected candidate pair. The secondary data used are daily stock prices starting from 6 days before and 7 days after the election event. Single sample t-test and pairs are used to test the hypothesis. The results of the study indicate that there is an abnormal return that occurs on the event date. In addition, empirical testing shows that there is a difference in abnormal returns, or abnormal, before and after the event date. Another thing also shows that the Indonesian capital market is relatively stable and not too affected by national political events if the event has been predicted in advance by investors. This indicates that other economic factors such as monetary policy, inflation rates, and industrial prospects have a more dominant influence than the results of the election dispute. For investors and capital market regulators, these results can serve as a reference that not all political events have a direct impact on stock market performance.